Peran Pembiayaan Mikro dalam Pengembangan UMKM Di Desa Situ Gadung Kabupaten Tangerang - Agus Suhartono; Agus Supriatna; Herlambang Herlambang (Perhimpunan Sarjana Ekonomi dan Bisnis, 2026)
Microfinance plays a significant role in supporting the growth and sustainability of Micro, Small, and Medium Enterprises (MSMEs), particularly in rural areas with limited access to formal financial institutions. This community service program (PKM) was conducted to enhance the understanding and capability of local traders in utilizing microfinance as a tool for business development in Situ Gadung Village, Tangerang Regency. The objective of this PKM activity was to increase participants’ knowledge of microfinance schemes and strengthen their skills in managing financing effectively to improve business performance. The program was carried out on 26 October 2025 by three lecturers from Universitas Pamulang and was attended by 23 local traders. The implementation method involved material presentation, hands-on practice, group discussions, and question-and-answer sessions. The PKM activities followed three stages: preparation, implementation, and reporting. The results show that participants gained improved understanding of microfinance concepts, were able to identify appropriate financing options, and demonstrated enhanced skills in applying basic financial management techniques to support their business growth. Overall, the program contributed to strengthening the financial literacy and business capacity of MSME actors in Situ Gadung Village.